Globalization and Social Justice in OECD Countries - Björn Kauder; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Social justice is a topic of importance to social scientists and also political decision makers. We examine the relationship between globalization and social justice as measured by a new indicator for 31 OECD countries. The results show that countries that experienced rapid globalization enjoy social justice. When the KOF index of globalization increases by one standard deviation, the social justice indicator increases by about 0.4 points (on a scale from 1 to 10). The policy implication is that permitting a national economy to become globally integrated is consistent with and promotes social justice.
Keywords: D63; F61; 330; globalization; social justice; economic integration